2002
DOI: 10.1016/s0735-1097(02)02063-6
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan benefits left ventricular structure and function in heart failure: Val-HeFT echocardiographic study

Abstract: The Val-HeFT echocardiographic substudy of 5,010 patients with moderate heart failure demonstrated that valsartan therapy taken with either ACEI or BB reversed LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(105 citation statements)
references
References 19 publications
4
98
0
3
Order By: Relevance
“…10,20,21 Thus, the vasodilatory effects of valsartan might have lowered arterial impedance in patients with the lowest SBP who would be expected to have the highest impedance, thereby increasing the cardiac output and maintaining blood pressure. Over the long term, valsartan use was associated with an improvement in LV ejection fraction 22 and a decrease in the levels of several neurohormones, including brain natriuretic peptide, norepinephrine, and aldosterone. 23,24 Thus, the dual effects of lowering impedance (BP-lowering effect) and improving LV structural remodeling might have contributed to the beneficial effects of valsartan on hemodynamics and subsequently to reduced morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…10,20,21 Thus, the vasodilatory effects of valsartan might have lowered arterial impedance in patients with the lowest SBP who would be expected to have the highest impedance, thereby increasing the cardiac output and maintaining blood pressure. Over the long term, valsartan use was associated with an improvement in LV ejection fraction 22 and a decrease in the levels of several neurohormones, including brain natriuretic peptide, norepinephrine, and aldosterone. 23,24 Thus, the dual effects of lowering impedance (BP-lowering effect) and improving LV structural remodeling might have contributed to the beneficial effects of valsartan on hemodynamics and subsequently to reduced morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inotropic agents decreased %FS. The original large-scale trials indicated that beta-blockers [4], ACEI [5,6], or ARB [5,6] decreased both mortality and morbidity in patients with CHF, while inotropic agents increased mortality. Also, an increase in %FS [7], and a decrease in either plasma BNP level [8,9] or ventricular dimensions [10] are intermediate endpoints that predict the decrease in mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…5 To date, a number of chronic HF medications have been shown to improve LV remodeling including β-adrenergic blockers (BB), angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and mineralocorticoid receptor antagonists. [6][7][8][9] Short of a single report, 5 however, little is known about the potential interplay between antiremodeling therapies and sST2 values in high-risk patients.…”
Section: Clinical Perspective On P 1213mentioning
confidence: 99%